2020
DOI: 10.1038/s41929-020-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

Operando identification of site-dependent water oxidation activity on ruthenium dioxide single-crystal surfaces

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
212
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(253 citation statements)
references
References 70 publications
14
212
1
Order By: Relevance
“…[42][43][44][45] Only a very recent contribution of Rao et al analyzed the differences in catalytic activity of the (110), (100) and (101) surfaces of RuO2. 46 Despite the limitations in solvent representation among others, 40,41 the computed overpotentials are in good agreement with experiments and they support that the WNA mechanism is usually the applied mechanism. Indeed, in the crystalline (110) surface the water nucleophilic attack to the oxo-species is computed to be kinetically easier than the oxo-coupling of the I2M, 39,41,56 which suggests that at least for this surface the WNA mechanism is preferred.…”
Section: Introductionmentioning
confidence: 54%
“…[42][43][44][45] Only a very recent contribution of Rao et al analyzed the differences in catalytic activity of the (110), (100) and (101) surfaces of RuO2. 46 Despite the limitations in solvent representation among others, 40,41 the computed overpotentials are in good agreement with experiments and they support that the WNA mechanism is usually the applied mechanism. Indeed, in the crystalline (110) surface the water nucleophilic attack to the oxo-species is computed to be kinetically easier than the oxo-coupling of the I2M, 39,41,56 which suggests that at least for this surface the WNA mechanism is preferred.…”
Section: Introductionmentioning
confidence: 54%
“…Based on HRTEM images (Figure S28, Supporting Information) of the derived Ru oxides and DFT calculations (Figures S42–S45, Supporting Information) of the OER mechanisms over different RuO2 surfaces, it can be concluded that the OER performance are the combined results of crystal surface, active surface area, and compositions. [ 40,53 ]…”
Section: Resultsmentioning
confidence: 99%
“…[23] More recently, Shao-Horn's group studied the critical role of metal-oxygen bonds in triggering lattice-oxygen oxidation [24] and the local environment of active site. [25] Further studies showed a strong correlation between OER activity and oxygen p-band center relative to the Fermi level through theoretical calculations. [26] Other parameters, including cations in octahedral sites and transition metal 3d -O 2p hybridization, have been widely studied by metal doping or partial element substitution.…”
Section: Introductionmentioning
confidence: 97%
“…first demonstrated the relationship between transition metal e g occupancy and OER activity [23] . More recently, Shao‐Horn's group studied the critical role of metal‐oxygen bonds in triggering lattice‐oxygen oxidation [24] and the local environment of active site [25] . Further studies showed a strong correlation between OER activity and oxygen p‐band center relative to the Fermi level through theoretical calculations [26] .…”
Section: Introductionmentioning
confidence: 99%